Low muscle strength, low bone mineral density, and high body mass index among adult special Olympics athletes: a cross-sectional examination - Cleveringa, M.; Pitchford, E. A. (Adapted Physical Activity Quarterly, 2023)
Adults with intellectual disabilities have increasing life expectancy but may be susceptible to early aging-related conditions. The purpose of this study was to examine associations between the presence of low muscle strength, low bone mineral density, and high body mass index with age and sex in adult Special Olympics athletes. Grip strength (n = 6,477; 40.9% female), chair stand time (n = 6,444; 40.5% female), body mass index (n = 7,824; 43.7% female), and bone mineral density (n = 3,091; 43.2% female) measurements were provided by Special Olympics International. Poor grip strength, chair stand time, bone mineral density, and body mass index were identified in 43.8%, 46.2%, 28.7%, and 50.3% of each sample, respectively. Increasing age was a risk factor for all conditions (odds ratio = 1.30-10.89; p < .05). High rates of adverse health conditions were observed in a sample of adults with intellectual disabilities. Increased risk was observed as early as the fourth decade of life.